A Convertible Spinal Orthosis for Controlled Torso Rigidity - Nicole I. Kern; Ronald J. Triolo; Rudi Kobetic; Musa Audu; Roger D. Quinn (Applied Bionics and Biomechanics)
A traditional spinal orthosis in conjunction with a hip-knee-ankle-foot orthosis (HKAFO) improves posture in persons with paraplegia during standing and walking. It also limits the wearer's range of motion when worn during other activities, such as vehicle transfer or sitting and reaching for objects. In order to regain full torso flexibility the user would need to remove the spinal orthosis which can be arduous and time consuming. A Convertible Spinal Orthosis (CSO) that allows the user to switch between Locked rigid torso support and Unlocked free motion has been designed, fabricated and tested. It shows promise for increasing functionality, wear time and subject comfort. Analysis of movement has been performed with an able-bodied and a paraplegic subject wearing a rigid spinal orthosis, the CSO in both states, and without any bracing. Configuration state had the most impact on lateral bending. Mean values for the paraplegic subject of 27°, 38°, 48°, and 48° and for the able-bodied subject of 22°, 26°, 48°, and 45° were found for lateral bending of the upper torso relative to the thighs in the Rigid, Locked, Unlocked, and No-Brace states, respectively.